Manfaat Stock opname Rumah dalam Proses terhadap Kesesuaian Pencatatan Aset Lancar: Studi Kasus pada PT ABCD Surabaya - Syaqna Salsabila Putri; Tantina Haryati (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the role of housing stock opname in ensuring the accuracy of current asset recording within a real estate company, using a case study at PT ABCD Surabaya. The issue addressed in this research stems from discrepancies between the physical condition of completed houses and their accounting records, caused by delays in administrative documentation such as contractor invoices and inspection reports. This study employs a descriptive qualitative approach, utilizing data collection methods including in-depth interviews, direct field observations, and internal company documentation. The findings indicate that stock opname not only serves to reconcile physical data with accounting records but also functions as a supervisory tool for construction progress, enhances contractor discipline, and reduces the risk of delayed asset recognition. Factors influencing the effectiveness of stock opname include the frequency of its implementation and the diligence of the executing staff. Appropriate frequency supports operational efficiency and improved asset control, while staff accuracy determines the reliability of the recorded data. The study concludes that stock opname is a strategic and multidimensional internal control instrument in managing housing inventory under construction. The study recommends revising operational stock opname procedures to be more responsive to project progress and enhancing staff capabilities through standardized training.